2010
DOI: 10.1111/j.1467-9604.2010.01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Sparking the imagination: creative experts working collaboratively with children, teachers and parents to enhance educational opportunities

Abstract: This article suggests that child poverty and unequal educational opportunity are inextricably linked. It is argued that even from an early age children from poorer backgrounds are disadvantaged in terms of their preparedness to thrive in the formal school environment. Educational achievement is strongly influenced by attitudes and much research suggests that children from less advantaged backgrounds feel less in control at school and lack confidence in performing traditional school tasks. The ‘Sparking the Ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Petrick (2014) highlighted that by growing up in poverty, the student was less likely to graduate from high school than students who grow up in a financially stable household. Further substantiating Petrick's research, Loughrey and Woods (2010) found that children who grew up in poverty began their educational path behind their peers skill-wise and rarely made academic gains to counter their losses, and, years later, the academic lag they acquired aided in the development of an accustomed lens that normalize subpar perceptions and performance.…”
Section: Poverty and Academic Achievementmentioning
confidence: 65%
See 1 more Smart Citation
“…Petrick (2014) highlighted that by growing up in poverty, the student was less likely to graduate from high school than students who grow up in a financially stable household. Further substantiating Petrick's research, Loughrey and Woods (2010) found that children who grew up in poverty began their educational path behind their peers skill-wise and rarely made academic gains to counter their losses, and, years later, the academic lag they acquired aided in the development of an accustomed lens that normalize subpar perceptions and performance.…”
Section: Poverty and Academic Achievementmentioning
confidence: 65%
“…Political candidates have used minority and poverty-based subgroups of students as a catapult for a heightened attention in the need for new reforms presidency after presidency. Within the literature, various components that weigh into the success of students' academics were discussed mentioning among others, the student's home life, poverty levels, and demands outside of the classroom (Chubb & Moe, 1990;Harrington, 2012;Loughrey & Woods, 2010;Messacar & Oreopoulous, 2013;Petrick, 2014). The teaming of the media, presidential candidates, and foundation members created a broadcast setting to deliberately manipulate the message delivered to the public (Knaak & Knaak, 2013;Ravitch, 2016) regarding America's academic standings on a global scale by omitting such external contributorsstudents living in poverty and minority studentsas evaluated in this study.…”
Section: Analysis Of the Federal Reform Initiativesmentioning
confidence: 99%
“…Such exercises could increase the motivation to learn. In the UK, school projects aimed at increasing students’ imagination and creativity have shown promising outcomes (Craft, 2000; Jeffrey & Woods, 2009; Loughrey & Woods, 2010). Loughrey and Woods demonstrated how disadvantaged children could develop positive attitudes toward school through different interventions in an arts-based curriculum.…”
Section: Discussionmentioning
confidence: 99%